ANALISIS TEORETIS TENTANG SELF- REGULATED LEARNING PADA PESERTA DIDIK BERKEBUTUHAN KHUSUS DALAM PENDIDIKAN INKLUSI - Mutiah Fauziah L; Ilmil Imani; Irdayanti; Hasmiati; Nurhasanah; Nurul Islamiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to theoretically analyze the concept of self-regulated learning (SRL) among students with special needs within the context of inclusive education. The research employs a qualitative approach through a literature review by examining relevant scholarly sources. The findings indicate that SRL is a crucial ability encompassing planning, monitoring, and self-reflection in the learning process. For students with special needs, the development of SRL is influenced by cognitive and motivational limitations as well as the level of support provided by the learning environment. The implementation of SRL in inclusive education requires adaptive instructional strategies, active teacher involvement, and a supportive environment to foster students’ independent learning. Therefore, SRL plays a strategic role in enhancing the quality of inclusive education. This study is expected to provide a conceptual foundation for developing more effective and student-centered learning models.